2003
DOI: 10.1590/s0103-97332003000200032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the break-up on the fusion and scattering processes

Abstract: We present results of the study of the influence of the break-up process on the fusion, scattering and reaction cross sections, at near barrier energies. Most of the discussed reactions and scattering mechanisms are induced by the stable weakly bound nuclei 6,7 Li and 9 Be, although comparisons with reactions induced by strongly bound nuclei are also made. We give a picture of the break-up and fusion mechanisms at energies above the Coulomb barrier.The effects of the coupling of elastic, inelastic and transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The influence of the break-up on the fusion cross section with medium -light mass nuclei was investigated by the comparison of the fusion excitation functions of several systems, at above barrier energies: the weakly bound 6,7 Li and 9 Be, and the tightly bound 16,17,18 Li was also measured. Several light systems measured by the gamma ray spectroscopy method by Mukherjee et al [19] were also analyzed.…”
mentioning
confidence: 99%
“…The influence of the break-up on the fusion cross section with medium -light mass nuclei was investigated by the comparison of the fusion excitation functions of several systems, at above barrier energies: the weakly bound 6,7 Li and 9 Be, and the tightly bound 16,17,18 Li was also measured. Several light systems measured by the gamma ray spectroscopy method by Mukherjee et al [19] were also analyzed.…”
mentioning
confidence: 99%
“…The reduced fusion excitation functions for the 6,7 Li, 9 Be, 16O + 64 Zn systems coincide. 30), 33) The same behavior is found when we compare the excitation functions of the 6,7 Li, 9 Be, 11 B, 16 O + 27 Al systems; 9 Be + 27 Al, 29 Si and 11 B + 27 Al systems (the last one leads to the same compound nucleus as 9 Be + 29 Si); 18 O + 10 B, 17 O + 11 B, 19 F + 9 Be (leading to the same compound nucleus); 19 F + 9 Be and 19 F + 12 C. 32), 33) The data for the 12 C + 7 Li reaction, 34) measured in inverse kinematics in order to minimize the problems of transmission of the low energy residues through the detector window, agree with those from the gamma spectroscopy method, 35)- 39) where no fusion suppression could be detected at energies above the Coulomb barrier. Therefore, we believe that there are strong signatures that the BU process does not affect the TF cross section, at above barrier energies, for these medium and light mass systems, and there is also some evidence that the ICF process is negligible, within the 10% uncertainties of the data, at this mass range.…”
Section: Discussion Of the Effect Of The Break-up On The Fusion Crossmentioning
confidence: 99%
“…23)-25) Barrier distributions were also derived. The total fusion (CF + ICF) cross sections of 6,7 Li + 64 Zn, 27 Al and 9 Be + 27 Al were measured at TANDAR by either time of flight 29), 33) or ionization chamber techniques. 32) The fusion of 9 Be + 64 Zn was measured at USP by the in-beam and off-beam gamma ray spectroscopy methods, 30), 31) and it was derived that the ICF cross section was smaller than 10% of the CF.…”
Section: Fusion Cross Section Data Obtained By Our Group In Collaboramentioning
confidence: 99%
“…At São Paulo, the elastic scattering was measured with the same set of nine surface barrier detectors used in previous work on the investigation of the threshold anomaly in the scattering of weakly [9,20,23,24] and tightly [28,29] bound nuclei. The detectors were placed at 40 cm from the target, with 5°angular separations between two adjacent detectors and a resolution of the order of 350 keV.…”
Section: Methodsmentioning
confidence: 99%
“…Important differences between these two lithium isotopes are the strong deformation of 7 Li, the much higher break-up ͑␣ + t͒ threshold energy, 2.47 MeV, and one bound excited state at 0.48 MeV. Keeley et al [18,19] suggested that the presence of the anomaly is due to inelastic and transfer channels, when reacting with 208 Pb, whereas Lubian et al [20] have shown that the anomaly disappears when only the coupling of the 7 Li excited state is considered in the scattering on 138 Ba. Recently, the scattering of radioactive 8 Li on 208 Pb was studied [21,22], and there were no signatures for the presence of the anomaly.…”
Section: Introductionmentioning
confidence: 99%